Premenstrual syndrome and premenstrual dysphoric disorder – problem on the border of psychiatry and gynecology - Olajossy, Marcin; Gerhant, Aneta (Current Problems of Psychiatry, 2011)
Many women in their reproductive years experiance some somatic and emotional symptoms in luteal phase of menstrual cycle. Clinically significant premenstrual symptoms occur in at least 20% of them. Many women in this group meet diagnostic criteria for premenstrual syndrom (PMS). Premenstrual disphoric disorder (PMDD) represents the more severe and disabling spectrum of premenstrual syndrome and occurs in an estimated 5% to 8% of menstruating women. The diagnosis of PMS/PMDD should be confirm by prospective symptoms charting in 2 menstrual cycles. It is essential to exclude other somatic or psychiatric disorders which symptoms can aggravate in luteal phase of cycle. The precise etiology of premenstrual syndroms is currently unknown. Recent evidence suggest that hypersensitivity to cyclical variations in level of gonadal hormones can predispose to PMS/PMDD. Dysregulation of serotoninergic and gabaergic neurotransmition are propably the consequence of this phenomenon. Several effective treatment option of that syndroms exist: serotoninergic antidepresant medications (selective serotonin reuptake inhibitors, venlafaxin, clomipramin), oral contraceptives that contain drosperinon and GnHR agonists. The present article provide a brief review of current information on the epidemiology, neurobiology and treatment of PMS/PMDD.